Results of spica cast in treatment of developmental dysplasia of the hip in children between 6-18 Months (مجلة البحوث الأكاديمية, 2026)
Background: Developmental dysplasia of the hip (DDH) includes a range of abnormalities from acetabular dysplasia to hip dislocation. Early diagnosis and treatment are essential to achieve good hip function and prevent early degenerative changes. When bracing fails, closed reduction and hip spica casting are commonly used in infants. Delayed treatment may lead to structural changes such as inverted labrum, hypertrophied ligamentum teres, pulvinar tissue, and capsular tightening.Aim: To evaluate the outcomes of static long-leg hip spica casting in children aged 6–18 months diagnosed with DDH at Misurata Medical Center.Methods: Patients were treated with adductor tenotomy, closed reduction, and static long-leg hip spica cast. Hips were classified using the Tönnis system, and baseline acetabular index (AI) was grouped as 30°–35°, 36°–40°, and > 40°. Clinical outcomes were assessed with the modified McKay criteria, and radiological results with Severin’s classification.Results: Thirty-eight hips (29 patients) were evaluated. According to Severin classification, 70% showed good radiological results (grades I–II), while 30% were poor. Based on the modified McKay criteria, 89% achieved good clinical outcomes (types I–II). Avascular necrosis was observed in 3 hips (7.8%). The mean age at reduction was 6 months, and mean follow-up was 5 months. The average immobilization period in spica cast was 90 days.Conclusion: Closed reduction and static hip spica casting is a safe and effective method for treating DDH in children aged 6–18 months. Outcomes are influenced mainly by the pre-reduction hip position, initial acetabular index, and occurrence of avascular necrosis.